1956
DOI: 10.1149/1.2430173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Pressure on the Oxidation Rate of Cobalt

Abstract: Co was oxidized from 800 ~ to 1200~ in 0.013-27.2 atm O2. It oxidized in accordance with the parabolic rate law above 950~ and formed the single oxide, CoO, above 900~ Pressure increase accelerated the rate of oxidation. However, the oxidation rate eventually ceased to increase with increase of oxygen pressure at temperatures below 1150~ Theoretical considerations employing a vacancy saturation mechanism correlated the data. Photomicrographs of the oxide layer are included. Activation energy for the diffusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This route can be an optimal choice when a metal diffusion barrier is required (e.g., Cu interconnects). Route B is arguably more elegant since the MOF precursor layer is formed by the controlled oxidation of the metal line surface 4143 . Since this route results in the direct contact between the metal and the MOF, low metal ion diffusion through the dielectric is needed to avoid electrical reliability issues.…”
Section: Introductionmentioning
confidence: 99%
“…This route can be an optimal choice when a metal diffusion barrier is required (e.g., Cu interconnects). Route B is arguably more elegant since the MOF precursor layer is formed by the controlled oxidation of the metal line surface 4143 . Since this route results in the direct contact between the metal and the MOF, low metal ion diffusion through the dielectric is needed to avoid electrical reliability issues.…”
Section: Introductionmentioning
confidence: 99%
“…From the studies on the chemical diffusion [6,12,13,17,23,27,28,32,[47][48][49][50][51][52][53][54][55] and cobalt self-diffusion [3,16,[56][57][58][59], mostly performed at higher oxygen pressures, it transpires that the matter transport occurs mainly via single-ionized cobalt vacancies. A similar conclusion can be derived from the relation between the defect concentration, the diffusion coefficients, and the parabolic rate constants of cobalt oxidation [60][61][62][63][64]. However, it has been concluded that the total concentration of cobalt vacancies is higher than that resulting from the studies on the deviation from the stoichiometry [14,64].…”
mentioning
confidence: 57%
“…The appearance of such a zone in cobalt monoxide scales is illustrated in Fig. 3, where it appears to be distinctly more porous than the outer columnar regions of scale, a fact which has been commented on by many authors (9)(10)(11). However, it is always difficult to be sure to what extent such apparent porosity is merely a reflection on the metallographic damage sustained to sutn a fine equiaxed structure during polishing; the detailed structure of the section of an oxide which shows clearly the columnar and equiaxed structure of the two zones in nickel oxide is well illustrated by the recently published photomicrographs of Rhinesand Wolf (12), see Fig.…”
Section: Microstructura1 Features Ofmentioning
confidence: 74%